The electrochemical behavior of the NiTi alloy in different simulated body fluids - Hansen, Alana Witt (2016)
In order to improve the NiTi alloy biocompatibility, surface treatments become very important. Nevertheless, researchers use different solutions to simulate the body fluids in electrochemical assays, and the correlation between the obtained results is difficult and might not even be possible. The present paper evaluated the electrochemical behavior of polished NiTi surfaces exposed to different simulated body fluid solutions: Hanks solution, Hanks’ balanced salt (HBSS) solution, saline body fluid (SBF) solution, and Ringer solution. The electrochemical behavior of NiTi was evaluated by open circuit potential (OCP) and cyclic voltammetry tests. The surfaces of the samples were also characterized by scanning electron microscopy, which was performed after the electrochemical tests. The results demonstrated that the NiTi alloy shows the same corrosion mechanism (pitting) in all simulated body fluids that were studied. However, the corrosion potential changes for each electrolyte, being HBSS, SBF and Ringer the most corrosive solutions. Furthermore, the Hanks and HBSS solutions demonstrated good reproducibility of the electochemical results. Considering that the HBSS represents an extreme environment, this solution seems to be the most indicated to study the corrosion behavior of NiTi treated surfaces.